Atividades experimentais construtivistas no ensino de biologia - Sena, Nelber Roberto (2023)
This text refers to the master's dissertation, allocated to the line of research Educational Practices in Teaching Science and Mathematics, and explores experimentation and its expectations. The study starts from the need to propose a model of experimental activities for teaching Biology in Basic Education, based on a constructivist conception. The urgency referred to by this study points out that, generally, the experimental activity taught in schools follows the model present in the 1960s and 1970s; however, the current moment demands teaching proposals that prioritize the construction of knowledge and not just the execution of a set of procedures. These aspects lead to the central question of the research, expressed as follows: How can constructivist experimental activities assist in the teaching-learning process of Biology? Seeking to answer this question, the present study has as its general objective to develop and apply a set of experimental activities structured based on constructivist conceptions for the teaching of Biology, being organized in six meetings and applied in a public school in the capital of the state of Rondônia in the year 2023. To achieve this purpose, the set of experimental activities was structured based on what was proposed by Rosa (2011) and whose foundations are based on the constructivist conception. In addition to this basis, the set of experimental activities is guided by the use of different teaching strategies, supported by the guidelines of the BNCC. Methodologically, the research proposed in this study is characterized as a qualitative approach and participatory research. As an instrument for data collection, the following materials were used: a registration diary produced by the teacher-researcher, and materials produced by the students, such as a report and questionnaire. The analysis of the data produced is limited to the teaching episodes, investigating evidence of learning in each of them. The results indicate that constructivist experimental activities are important for students to build their scientific knowledge, formulate hypotheses in an attempt to solve problems, and value cooperation and teamwork. The Educational Product associated with this dissertation refers to a support text for the Biology teacher of the first year of High School involving a Set of Experimental Activities of constructivist conception. The referred Educational Product is available for free access on the EduCapes Portal http://educapes.capes.gov.br/handle/capes/741427, as well as on the program page www.upf.br/ppgecm and on the PPGECM educational products page www.upf.br/produtoseducacionais.